Mental health night: A peer-led initiative - Kearney, Hannah; Jones, Becky; Dai, Jia Hong; Burcul, Ivana (Canadian Medical Education Journal, 2020)
Implication Statement: We describe a peer-led mental health (MH) workshop that was held at the Michael G. DeGroote School of Medicine (Niagara Regional Campus) in collaboration with Student Affairs. Workshop aims included facilitating discussions among peers and engaging in case-based learning about MH experiences in medical school. Post-workshop, attendees reported increased comfort in talking to classmates about personal MH, recognizing MH crises, and asking for help from peers. We believe that engaging medical learners in MH discussions early on in medical education is critical, and that peer-led workshops may aid in decreasing future MH difficulties and burnout. Due to the low-cost of holding peer-led workshops, this event could be easily replicated at other training sites.